2014
DOI: 10.1021/jo501910q
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Regiocontrolled Domino Synthesis of N-Sulfonyl Dihydrophenanthridines and Dihydrodibenzo[c,e]azepines: Control over the Formation of Biaryl Sultams in the Intramolecular Direct Arylation

Abstract: A palladium-catalyzed domino N-benzylation/intramolecular direct arylation involving sulfonanilides and 2-bromobenzyl bromides has been developed for the first time, providing a workable access to N-sulfonyl dihydrophenanthridines in good to excellent yields. Under the optimized conditions, the formation of 5,6-dihydrophenanthridines was largely controlled over the formation of biaryl sultams containing a seven member ring. The optimized condition was found extendable to the regiocontrolled domino formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…[8] Recently, our group also developed a palladium-catalyzed intramolecular oxidative coupling strategy that involves C(sp 2 )-H double bonds for the synthesis of five-, [9] six-, [10] and seven-membered [10] (hetero)biaryl sultams by using AgOAc as a mild oxidant. Subsequently, Youn et al reported the competitive formation of seven-membered biaryl sultams in the ortho-C-H hydroxylation of N-sulfonylbenzylamines by using K 2 S 2 O 8 as a strong oxidant.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Recently, our group also developed a palladium-catalyzed intramolecular oxidative coupling strategy that involves C(sp 2 )-H double bonds for the synthesis of five-, [9] six-, [10] and seven-membered [10] (hetero)biaryl sultams by using AgOAc as a mild oxidant. Subsequently, Youn et al reported the competitive formation of seven-membered biaryl sultams in the ortho-C-H hydroxylation of N-sulfonylbenzylamines by using K 2 S 2 O 8 as a strong oxidant.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Laha and co‐workers synthesized the biaryl sultams 8.3 from sulfonamide derivatives 8.1 and 2‐bromobenzyl bromide derivatives 8.2 through Pd‐catalyzed regiocontrolled domino N ‐benzylation along with direct arylation (Scheme ) …”
Section: Synthesis Of Sultamsmentioning
confidence: 99%
“…Laha research group found that the formation of biaryl sultam could be avoided completely by using N‐Ms anilines. Finally, the synthesis of phenanthridines was achieved by deprotecting dihydrophenantridines with TBAF in acetonitrile reflux …”
Section: Pd‐catalyzed Intramolecular C–h Arylation (C–h/c–x Coupling)mentioning
confidence: 99%